Necrotising Candida oesophagitis after thoracic radiotherapy: significance of oesophageal wall oedema on CT. (1st July 2015) - Saito, Hirotake; Sueyama, Hiroo; Fukuda, Takanori; Ota, Kyuma
Abstract : Although oesophageal candidiasis is usually a superficial mucosal infection, necrotising Candida oesophagitis has been reported to cause oesophageal perforation or lung abscess. We report the case of an elderly Japanese man presenting with painless dysphagia after thoracic radiotherapy for oesophageal cancer. Non-contrast CT demonstrated segmental and oedematous thickening of the oesophageal wall. Endoscopy revealed white plaques on the oesophageal mucosa. The patient's oesophagitis responded to systemic antifungal therapy, and did not lead to oesophageal perforation. He died of recurrent oesophageal cancer several months later. The importance of severe radiation-induced oesophagitis without pain, our pathophysiological hypothesis on the local oedema caused by Candida infection and the usefulness of CT in evaluating abnormal thickening of the gastrointestinal tract are discussed separately in the article.